Penerapan Teori Behaviorisme dalam Pembelajaran - Rahmah, Nurul Wahidatur; Aly, Hery Noer (JOEAI (Journal of Education and Instruction), 2023)
This article examines the application of behaviorism to the study of learning. This article employs a literature study methodology to seek and discover solutions through a literature evaluation of books, journals, and researchers' direct observations. The study's findings demonstrate that the behaviorist perspective acknowledges the significance of stimulus input and response output. Behaviorism is a learning theory that stresses the study of behavior formation based on the relationship between observable stimuli and response and awareness and mental constructions. In conclusion, behaviorism learning theory contrasts with cognitive theory, which contends that the learning process is an invisible mental process. The behaviorist learning theory lays a strong emphasis on observable, measurable, and quantifiable behavioral changes as learning outcomes. Keywords: Understanding, Implementation, Behaviorism Theory